ETUDE EPIDEMIOLOGIQUE ET CLINIQUE DE LA TUBERCULOSEA L’HOPITAL GENERAL DE REFERENCE DE KINDUDU 1èr JANVIER 2020 AU 31 DECEMBRE 2021 - Numbi Alexis, Kabange; Djela Benjamin, Wendjikulu (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Research carried out at the HGR/Kindu on the “epidemiological and clinical study of tuberculosis” led to the following observations:The prevalence of tuberculosis was 0.7 and the male sex was the most affected with 59.3The most affected age group was between 15 and 24 years old with 19.3TPM was the most observed form with 59.3therapeutic success and treatment completed at 45 each;Tuberculosis being a reality at HGR/Kindu, requires sustained attention from the political and health authorities.